2006
DOI: 10.1534/genetics.105.048793
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Hsp70 in Drosophila Is Pleiotropic, With Effects on Thermotolerance, Recovery From Heat Shock and Neurodegeneration

Abstract: The heat-shock response is a programmed change in gene expression carried out by cells in response to environmental stress, such as heat. This response is universal and is characterized by the synthesis of a small group of conserved protein chaperones. In Drosophila melanogaster the Hsp70 chaperone dominates the profile of protein synthesis during the heat-shock response. We recently generated precise deletion alleles of the Hsp70 genes of D. melanogaster and have used those alleles to characterize the phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
107
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(115 citation statements)
references
References 131 publications
(123 reference statements)
8
107
0
Order By: Relevance
“…Herein, we also suggest that the downregulation of hsp22 found in all the investigated strains may also underlie the maintenance of some degree of genomic tolerance for surviving, as previously suggested by Gong and Golic (2006). This could mean that hsp22 may play an important role in the plasticity of genome adaptation.…”
Section: Discussionsupporting
confidence: 78%
“…Herein, we also suggest that the downregulation of hsp22 found in all the investigated strains may also underlie the maintenance of some degree of genomic tolerance for surviving, as previously suggested by Gong and Golic (2006). This could mean that hsp22 may play an important role in the plasticity of genome adaptation.…”
Section: Discussionsupporting
confidence: 78%
“…Common elements may underlie general mechanisms of stress tolerance (Kültz, 2005). For example, Hsp proteins are key players in conferring tolerance to nearly all kinds of stresses Whitman, 2009), including heat (Welte et al, 1993;Feder, 1999;Gong and Golic, 2006) and cold stress (Colinet et al, 2010b;Kostál and Tollarova-Borovanska, 2009;Rinehart et al, 2007). Thus, hsp genes represent prime candidates for investigating molecular correlates at young age.…”
Section: The Journal Of Experimental Biology 216 (2)mentioning
confidence: 99%
“…The HSP70 family is one of the most thoroughly studied groups. The lack of HSP70 expression in Drosophila results in reduced heat resistance and developmental delays, indicating that the HSP70 gene plays an important role in heat shock (Gong and Golic, 2006). Shabtay and Arad (2006) observed that differential combinations of HSFs and DNA have varying effects on HSP transcription and translation.…”
Section: Introductionmentioning
confidence: 99%